The plant ionome revisited by the nutrient balance concept - Parent, Serge-Etienne; Parent, Leon Etienne; Jose Egozcue, Juan; Rozane, Danilo-Eduardo [UNESP]; Hernandes, Amanda [UNESP]; Lapointe, Line; Hebert-Gentile, Valerie; Naess, Kristine; Marchand, Sebastien; Lafond, Jean; Mattos, Dirceu; Barlow, Philip; et al. (Frontiers Research Foundation, 2013)
Tissue analysis is commonly used in ecology and agronomy to portray plant nutrient signatures. Nutrient concentration data, or ionomes, belong to the compositional data class, i.e., multivariate data that are proportions of some whole, hence carrying important numerical properties. Statistics computed across raw or ordinary log-transformed nutrient data are intrinsically biased, hence possibly leading to wrong inferences. Our objective was to present a sound and robust approach based on a novel nutrient balance concept to classify plant ionomes. We analyzed leaf N, R K, Ca, and Mg of two wild and six domesticated fruit species from Canada, Brazil, and New Zealand sampled during reproductive stages. Nutrient concentrations were (1) analyzed without transformation, (2) ordinary log-transformed as commonly but incorrectly applied in practice, (3) additive log-ratio (air) transformed as surrogate to stoichiometric rules, and (4) converted to isometric log-ratios OH arranged as sound nutrient balance variables. Raw concentration and ordinary log transformation both led to biased multivariate analysis due to redundancy between interacting nutrients. The air- and ilr-transformed data provided unbiased discriminant analyses of plant ionomes, where wild and domesticated species formed distinct groups and the ionomes of species and cultivars were differentiated without numerical bias. The ilr nutrient balance concept is preferable to air, because the ilr technique projects the most important interactions between nutrients into a convenient Euclidean space.This novel numerical approach allows rectifying historical biases and supervising phenotypic plasticity in plant nutrition studies.
Keywords: compositional data analysis; ionome classification; nutrient interactions; numerical biases; isometric log-ratio; Plant nutrition